Fast and efficient generation of oligodendrocytes from human induced pluripotent stem cells (hiPSCs) - García-León, Juan Antonio; Cáceres Palomo, Laura; Dávila-Cansino, José Carlos; Vitorica Ferrández, Javier; Verfaillie, Catherine M.; Gutiérrez-Pérez, Antonia (Wiley, 2021)
Oligodendrocytes (OLs) are highly specialized cells of the central nervous system responsible for myelin production and metabolic support of neurons. Defects in OLs are crucial in several neurodegenerative diseases including multiple sclerosis (MS) and amyotrophic lateral sclerosis (ALS). Scarce access to primary samples and lack of efficient protocols to generate OLs from human pluripotent stem cells (hPSCs) are hampering our understanding of OL biology and the development of novel therapies. To promote the conversion of hPSCs into OLs, we have screened for a number of transcription factors (TFs) previously reported to be involved in OL generation. We found that the overexpression of SOX10 was sufficient to generate O4+ oligodendrocyte precursor cells (OPCs) from hPSCs only 10 days after SOX10 induction. Generated OPCs expressed mature OL proteins as MBP or MOG. At the transcriptome level, generated OPCs resembled primary OPCs. To test the functionality of generated OPCs, O4+ cells were co-cultured together with neurons, finding that O4+ cells were able to myelinate the neurons. Moreover, O4+ cells were injected intracerebrally in newborn shiverer RAG2-/- mice, finding that generated OLs extended within the corpus callosum and generated functional myelin, demonstrating the functionality of generated cells also in vivo. The protocol also describes an alternative for viral transduction, by incorporating an inducible SOX10 in the safe harbor locus AAVS1, yielding ~100% pure OPCs. O4+ OPCs can be co-cultured with maturing hPSC-derived neurons in 96/384-well- format plates, allowing the screening of pro-myelinating compounds. We have developed a novel methodology for a fast (20 days from hPSC stage) and efficient generation of functional OLs, which allow testing of compounds involved in myelination. This technology will allow further studies to better understand human OL biology and the screening of potential compounds involved in myelination in a human setting.
Acknowledgments: This study was supported by Instituto de Salud Carlos III (ISCiii) of Spain, co-financed by FEDER funds from European Union, through grants PI18/01557 (to AG), PI18/01556 (to JV), and CIBERNED (CB06/05/1116 to AG and CB06/05/0094 to JV); by Junta de Andalucia through Consejería de Economía y Conocimiento grants UMA18-FEDERJA-211 (to AG), PY18-RT-2233 (to AG) and US-1262734 (to JV) co-financed by Programa Operativo FEDER 2014-2020 and Consejeria de Salud grant PI-0276-2018 (to JAGL).
Keywords: Neuroglia; Alzheimer; iPSC; oligodendrocytes; Oligodendrocytes